Surgical resection of macrocystic lymphatic malformations of the head and neck: Short and long-term outcomes. (July 2020) - Bonilla-Velez, Juliana; Moore, Brendan P.; Cleves, Mario A.; Buckmiller, Lisa; Richter, Gresham T.
Abstract: Background: Controversy exists on management of lymphatic malformations, with schools of thought advocating for observation, surgery or sclerotherapy. This study sought to examine outcomes after surgical resection of pediatric cervicofacial macrocystic lymphatic malformations (MLM). Methods: Case series with planned data collection on pediatric patients with cervicofacial MLM who underwent surgical resection at a tertiary referral center for vascular anomalies from January 1995 to June 2016. For consistency in patient population analysis, patients who had pre-surgical sclerotherapy or had mixed or microcystic disease were excluded. The main outcome was complete response rate (CR) and long-term recurrence-free survival (RFS). Results: Sixty-three patients who underwent excision of MLM were included, 52.4% were female, 77.8% Caucasian. The majority had de Serres stage I-III (96.8%) affecting the neck (71.4%). Patients were discharged the same day (28.6%), or had a 1 day median length-of-stay (interquartile range (IQR) = 2). Surgical complications included seroma/hematoma (9.5%), transient nerve weakness (facial nerve, sympathetic chain, or phrenic nerve, 6.3%), and infection (1.6%). On long-term follow-up (median: 12 months, IQR 1–43 months), a single surgery achieved CR in 90.5% of patients. RFS was achieved in 86% of patients in our observation period of up to 15 years. Most patients requiring a second intervention failed within 6-months of initial procedure (4/5 patients, 90%); associated factors included bilaterality, advanced staging, and partial response at first-follow-up (p = 0.0051, 0.0051, and <0.0001, respectively). Conclusions: Surgery is safe and effective as first line treatment for selected MLM. For stage I-III MLM CR and long-term RFS can be achieved with a single surgery. A direct and randomized comparison of treatment modalities is needed.